2010
DOI: 10.2353/jmoldx.2010.090220
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate, Clinically Feasible Multi-Gene Expression Assay for Predicting Metastasis in Uveal Melanoma

Abstract: Uveal (ocular) melanoma is an aggressive cancer that often forms undetectable micrometastases before diagnosis of the primary tumor. These micrometastases later multiply to generate metastatic tumors that are resistant to therapy and are uniformly fatal. We have previously identified a gene expression profile derived from the primary tumor that is extremely accurate for identifying patients at high risk of metastatic disease. Development of a practical clinically feasible platform for analyzing this expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
275
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 308 publications
(282 citation statements)
references
References 34 publications
4
275
0
1
Order By: Relevance
“…[21][22][23] Genetic prognostication Genetic analysis provides the single best estimate for the risk of metastasis from uveal melanoma. 12,24,25 Such an analysis can be performed by charting chromosomal alternations 26,27 or by gene expression profiling. 24,25,28 The latest TNM edition encourages recording of genetic features.…”
Section: Prognosis Of the Primary Tumourmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23] Genetic prognostication Genetic analysis provides the single best estimate for the risk of metastasis from uveal melanoma. 12,24,25 Such an analysis can be performed by charting chromosomal alternations 26,27 or by gene expression profiling. 24,25,28 The latest TNM edition encourages recording of genetic features.…”
Section: Prognosis Of the Primary Tumourmentioning
confidence: 99%
“…12,24,25 Such an analysis can be performed by charting chromosomal alternations 26,27 or by gene expression profiling. 24,25,28 The latest TNM edition encourages recording of genetic features. 9 A major breakthrough was the observation that many uveal melanomas lack one copy of chromosome 3, and that these monosomic tumours are usually those that metastatise.…”
Section: Prognosis Of the Primary Tumourmentioning
confidence: 99%
See 1 more Smart Citation
“…Two genetic tests more precisely identify patients with worse prognosis: testing for monosomy 3 and gene-expression profiling (gep). Monosomy 3, with a gain in chromosome 8q, and gep class 2 are associated with 3-year metastasis-free survival rates of 53% and 50% respectively 8,13,14 ; these genetic variations occur in about 50% of patients 13,[15][16][17][18] . A prospective validation study of gep class 2 showed that, on multivariate analysis, gep class was the only significant factor 14 .…”
Section: Introductionmentioning
confidence: 99%
“…21 A proprietary GEP assay using a microarray of only 13 genes has been reported to be the most accurate prognostic marker for melanoma mortality and metastasis, although this remains controversial. 22,23 Although greatly inferior to chromosomal analysis and GEP, clinical examination and routine histopathological examination of uveal melanoma can reveal a number of important prognostic factors. Tumor size (largest tumor diameter and thickness) and the presence or absence of ciliary body involvement and extraocular extension are the most important factors that can be determined on clinical examination.…”
mentioning
confidence: 99%